PENGUKURAN PROBABILITAS KEBANGKRUTAN OBLIGASI KORPORASI DENGAN SUKU BUNGA VASICEK MODEL MERTON (Studi Kasus Obligasi PT Bank Lampung, Tbk) - Kumo Ratih; Di Asih I Maruddani; Abdul Hoyyi (Jurnal Gaussian, 2012)
Bond is one of financial instrument that have lower investment risk than stock. One of investment risk is credit risk. Its refers to the risk due to unexpected changes in the credit quality of a counterparty or issuer on maturity date. There are two ways in the modelling of credit risk, structural model and reduced models. The structural model introduced by Black-Scholes (1973) and Merton (1974). On the Merton model assume that default occurs when the firm can not pay the coupon or face value at the maturity date. The interest rate on this model asssumed following Vasicek rate. An empirical study using corporate bond of PT Bank Lampung, Tbk with 300 billion face value. Value of Probability of Default 0,0000007910811% provethat PT Bank Lampung still can full their obigation at November 2012.